"We were trying to do quality versus quantity": Challenges and opportunities at the intersection of standardized and personalized social care in community health centers - Sara L. Ackerman; Holly Wing; Benjamín Aceves; Maura Pisciotta; Danielle Hessler; Laura M. Gottlieb (Elsevier, 2023)
A growing number of clinics are adopting standardized "social risk" screening and referral programs with the goal of mitigating adversities that negatively influence patients' health. We examined efforts to integrate social risk programs into community health centers (CHCs) providing primary care services in Oregon. CHCs participated in either one or both of two large initiatives aiming to embed standardized social risk screening and referral procedures. We conducted 42 semi-structured interviews with clinicians, managers and staff at 12 clinics affiliated with five CHCs to understand implementation processes and roadblocks. Thematic analysis drew on Normalization Process Theory (NPT) to elucidate the dynamic, interactional nature of efforts to integrate a complex sociotechnical intervention. We found that standardized social care was anticipated to align well with institutional commitments and priorities. However, competing priorities, staff turnover, and uncertainties about roles and responsibilities contributed to difficulties sustaining support among staff. Although participating clinics found benefits and challenges in adopting standardized social care practices, the new tools were often modified or abandoned in order to preserve the advantages of already-embedded social care practices. Across clinics, the relationship between standardized procedures, and existing social care activities, played an important role in patterns of adoption, non-adoption and adaptation, with standardized tools often experienced as undermining more relational, team-based social care. As screening and referral platforms are taken up by community health centers, the locally specific and largely undocumented forms of social care developed by clinics need to be better understood and accounted for in large-scale implementation efforts.